EFEKTIVITAS TERAPI FARMAKOLOGIS DAN NONFARMAKOLOGIS TERHADAP NYERI HAID (DISMINORE) PADA SISWI XI DI SMA NEGERI 1 PEMANGKAT - ., Wulan Purnama Sari (ProNers, 2014)
Disminore is cramping, pain and other discomfort associated with menstruation. One of the interventions toaddress dysmenorrhea is using pharmacological therapy and non-pharmacological therapies, where aspharmacological analgesic drug classes using non steroidal anti inflammatory drugs (NSAIDs) and nonpharmacologicaltherapies can use warm compresses and aromatherapy. This study was conducted toexamine the effectiveness of pharmacological therapy and non-pharmacological to overcome dysmenorrheain adolescent girls. This study used a quantitative research approach and quasi-experimental one group preand post test design with control group. Purposive sampling technique was used to collect the sample, thenumber of obtained   samples was 20 respondents get the young women ages 16-17 years. The statistical testused paired t-tests for non-pharmacological groups and independent t-tests test for pharmacological and nonpharmacologicalgroups.Painscalebeforetheinterventionwasintheinterval8-10.Initially,themajorityofthesamples in both group had a pain scale includes of 9 (50%) which up to 10 respondents. After theimplementation of pharmacological therapy and non-pharmacological therapy, the pain intensity wasreduced to mild intensity which was comprised to 70% of the respondent. Test results of paired t-tests after anon-pharmacological therapy (warm compresses and jasmine aromatherapy) showed a significant differencesbetween dysmenorrhea before and after the with p value t 0.00 and 11.00. While the results of independent ttesttest between pharmacological and non-pharmacological that there were differences in the averagedecrease in the p value disminore 0.01 (0.29 -2.10). This study concludes that both non-pharmacologictherapy and pharmacological therapy have been effective in reducing menstrual pain. As a result, thatcomplementary therapies and aromatherapy warm compress can be an alternative non-drug therapy to reducemenstrual pain. Keywords : Disminore, pharmacological therapy, warm compresses, aromatherapy.